Congenital cytomegalovirus infection: the state of the art and future perspectives - Salomè, S.; Corrado, F. R.; Mazzarelli, L. L.; Maruotti, G. M.; Capasso, L.; Blazquez-Gamero, D.; Raimondi, F. (Frontiers in Pediatrics, 2023)
Congenital cytomegalovirus (cCMV) infection is the most common congenital infection, with an estimated incidence of approximately one in 200 infants in high-income settings. Approximately one in four children may experience life-long consequences, including sensorineural hearing loss and neurodisability. Knowledge regarding prevention, diagnosis, and treatment increased in the recent years, but some challenges remain. In this review, we tried to summarize the current knowledge on both the obstetrical and pediatric areas, while also highlighting controversial aspects and future perspectives. There is a need to enhance awareness among the general population and pregnant women through specific information programs. Further research is needed to better define the classification of individuals at birth and to have a deeper understanding of the long-term outcomes for so defined children. Finally, the availability of valaciclovir medication throughout pregnancy, where appropriate, has prompted the assessment of a universal serological antenatal screening. It is recommended to establish a dedicated unit for better evaluation and management of both mothers and children.